LUAS PENGUNGKAPAN SUKARELA, ASIMETRI INFORMASI,DAN BIAYA MODAL EKUITAS - Novita Adeliana Darma (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2017)
This study examines the effect of voluntary disclosure on the cost of equity capita lwith information asymmetry as an intervening variablein manufacturing companies listed in Indonesia Stock Exchange in the period of 2008-2012. The total population of this study were 203 companies. The research hypotheses were tested using path analysis model with unbalanced panel data. The study concluded that the voluntary disclosure had indirect effect on the cost of equity capital by the information asymmetry as an intervening variable.Keywords: Voluntary Disclosure, InformationAsymmetry, Cost Of EquityCapital